2002
DOI: 10.1021/jf025747i
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Ochratoxin A by Fungi Isolated from Grapes

Abstract: Ochratoxin A is a mycotoxin present in several food products for which levels should be reduced. Chemical, physical, and biological methods have been proposed for the detoxification of mycotoxins, biological methods being the more promising ones. In this report, filamentous fungi isolated from Portuguese grapes were assessed for ochratoxin A degradation capabilities. It was observed that 51 of the 76 tested strains, predominantly aspergillus species, were able to degrade more than 80% of ochratoxin A added to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 18 publications
(19 reference statements)
6
107
0
2
Order By: Relevance
“…OTA detoxification with chemical compounds such as activated charcoal, cholestyramine, sodium and calcium aluminium silicates (mainly zeolites), bentonite, wood fragments or yeast [262][263][264][265][266][267][268][269][270][271][272] has been tested. Some of these compounds were tested in vivo; however, their activity was not as high as expected except for the activated charcoal [269].…”
Section: Chemical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…OTA detoxification with chemical compounds such as activated charcoal, cholestyramine, sodium and calcium aluminium silicates (mainly zeolites), bentonite, wood fragments or yeast [262][263][264][265][266][267][268][269][270][271][272] has been tested. Some of these compounds were tested in vivo; however, their activity was not as high as expected except for the activated charcoal [269].…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Activated charcoal use, however, has been rejected due to the essential nutrient retention and animal poisoning [270]. Wine fining agents such as potassium caseinate or activated carbon have shown positive effects on OTA detoxification (reduction up to 82%) but they have also damaged wine quality [271,272]. A new insoluble vegetal fibre has been developed in order to adsorb the OTA present in liquid food products or, in the case of beer, present during the brewing step [273].…”
Section: Chemical Methodsmentioning
confidence: 99%
“…[85], Aspergillus spp. [86,87,88,89], Pleurotus ostreatus [90] and Trichosporon [91]). Among microbial populations involved in food production, especially those involved in beer brewing [92,93,94] or yoghurt production (e.g., Streptococcus salivarius , Lactobacillus delbruecki [95]) have been shown to degrade OTA to some extent.…”
Section: Degradation Of Ochratoxin a In Ruminantsmentioning
confidence: 99%
“…Recently, an increase in the research connected with mycotoxin detoxification by microorganisms has been observed. Several studies showed that some bacteria, moulds, and yeasts, for example Lactobacillus acidophilus, Bifidobacterium animalis, Oenococcus oeni, Aspergillus niger, A. carbonarius, A. fumigatus, Saccharomyces cerevisiae, and Kloeckera apiculata are able to detoxify mycotoxins [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%